2018
DOI: 10.1016/j.compositesb.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of carbon fibre-reinforced polymer composites through radon-transform analysis of complex eddy-current data

Abstract: Maintaining the correct fibre orientations and stacking sequence in carbon-fibre reinforced polymers (CFRP) during manufacture is essential for achieving the required mechanical properties of a component. This paper presents and evaluates a method for the rapid characterisation of the fibre orientations present in CFRP structures, and the differentiation of different stacking sequences, through the Radon-transform analysis of complex-valued eddy-current testing (ECT) inspection data. A high-frequency (20 MHz) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…A unidirectional CFRP plate with a 135 × 135 × 1.44 mm 3 was fabricated with six plies of prepreg (Torayca P3252S-25, Toray Industries Inc.). The six prepregs were laminated on the base plate and compressed at 0.5 MPa and heated at 130°C for 60 min by using a hot press machine (AH-2003, ASONE Co.).…”
Section: Materials and Methods (A) Cfrp Having In-plane Wavinessmentioning
confidence: 99%
See 1 more Smart Citation
“…A unidirectional CFRP plate with a 135 × 135 × 1.44 mm 3 was fabricated with six plies of prepreg (Torayca P3252S-25, Toray Industries Inc.). The six prepregs were laminated on the base plate and compressed at 0.5 MPa and heated at 130°C for 60 min by using a hot press machine (AH-2003, ASONE Co.).…”
Section: Materials and Methods (A) Cfrp Having In-plane Wavinessmentioning
confidence: 99%
“…By contrast, eddy current testing (ECT) can be suited to those fibre-related defects because it is susceptible to the variation of electric resistance. For instance, it is reported that fibre orientation [1][2][3][4][5][6][7][8][9][10], misorientation (off-axis) [11][12][13][14][15] and fibre waviness [16][17][18][19][20][21] are detectable fibre-related defects by ECT. Additionally, some researchers have reported that ECT with higher frequency has the potential to non-destructively evaluate the hardening degree of matrix resin in FRP during the curing process of products [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Non-destructive detection and identification of damage in CFRPs has been done using conductivity measurements [39,40,49,83,94,95], and eddy current measurements [96][97][98][99][100][101][102][103][104][105][106]. Schueler et al [40] used multiple probes and created a finite element model of a small composite to detect where and what damage was in the composite.…”
Section: Structural Health Monitoringmentioning
confidence: 99%
“…ECT can be used in several ways to inspect carbon fibre composites [13]. It is typically used for inspecting undulations in carbon fibre reinforcement fabrics, quality control of stacking sequence, fibre orientation and curing effects [14][15][16]. Electrical properties can be characterized through various orientations with ECT techniques [17,18].…”
Section: Introductionmentioning
confidence: 99%